2019
DOI: 10.3389/fneur.2019.00596
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Treatment, and Outcomes Among Chinese Children With Anti-methyl-D-aspartate Receptor (Anti-NMDAR) Encephalitis

Abstract: Objective: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is the most common form of autoimmune encephalitis in pediatric patients. In this study, we aimed to investigate the clinical features and long-term outcomes of pediatric patients with anti-NMDAR encephalitis in China. Methods: We conducted a retrospective study of children (age range: 0–18 years) with anti-NMDAR encephalitis treated at Children's Hospital of Fudan University between July 2015 and Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 45 publications
4
30
0
3
Order By: Relevance
“…In this present study, we described the clinical features, auxiliary examination features, treatment protocols and clinical outcomes of eight Chinese children treated with rituximab. All eight children had no detectable neoplasm supporting previous reports that pediatric patients are less likely to have associated tumors (1,(15)(16)(17)(18). Rituximab was administered as a second-line immunosuppressant after a median of 57 days of disease which was longer than other report at 0.1 months (2).…”
Section: Discussionsupporting
confidence: 74%
“…In this present study, we described the clinical features, auxiliary examination features, treatment protocols and clinical outcomes of eight Chinese children treated with rituximab. All eight children had no detectable neoplasm supporting previous reports that pediatric patients are less likely to have associated tumors (1,(15)(16)(17)(18). Rituximab was administered as a second-line immunosuppressant after a median of 57 days of disease which was longer than other report at 0.1 months (2).…”
Section: Discussionsupporting
confidence: 74%
“…However, only 8.39% of the patients in our cohort had a tumor, with ovarian teratoma comprising 84.2% of the tumors diagnosed in females. Other studies of Chinese or Asian cohorts have also reported a relatively low prevalence of tumors ( Supplementary Table 4 ) [Lim et al ( 24 ), 22.7%; Wang et al ( 25 ), 8%; Liu et al ( 22 ), 6.7%; Zhang et al ( 26 ), 8.1%]. The heterogeneity among Asian and Western populations might be due to different genetic backgrounds and epidemiologic factors.…”
Section: Discussionmentioning
confidence: 86%
“…Only one child in the ADEM with MOG-abs group was positive for anti-NMDAR antibodies in serum and CSF (1:320 in the serum and 1:3.2 in the CSF). However, the clinical presentation, cerebral MRI, clinical course, and prognosis were more in line with ADEM than with anti-NMDAR encephalitis ( 12 ). The median time from symptom onset to EEG recording was 25.5 (range: 4–57) days and 11.5 (range: 4–49) days in patients with MOG-abs and without MOG-abs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical outcomes were evaluated based on mRS before immunotherapy and during clinical visits to the neurologist or through a telephone interview after discharge. The evaluation standards were as follows: full recovery, mRS of 0; mild deficits, mRS of 1–2; severe deficits, mRS of 3–5; or death, mRS of 6 ( 12 ). We defined clinical improvement as an increase of 1 in mRS and clinical recovery as an mRS of 0–2.…”
Section: Methodsmentioning
confidence: 99%